Communication Function of Elections - Turska-Kawa, Agnieszka; Wojtasik, Waldemar (Communication Today, 2025)
The aim of the text is to describe one of the basic functions of the elections, executed at both normative and empirical levels – the communication function, in the context of changes in the structure of Western societies, changes in methods and strategies of political communication and evolution of forms of electoral participation. Nowadays, as the communication function is meant as the establishment of such an interaction between the actors of the electoral process, which by means of non-accidental messages and communication channels guide the decisions of voters. The authors also aim to describe the process of character transformation of the communication function of elections, resulting from changes in the political sphere and its axiological layer.